College Student Alcohol Consumption, Day of the Week, and Class Schedule - Wood, Phillip K.; Sher, Kenneth J.; Rutledge, Patricia C. (Alcoholism, clinical and experimental research, 2007)
Background: For many college students, Friday class schedules may contribute to weekend‐like drinking behaviors beginning on Thursday. This study characterizes college students' daily alcohol consumption patterns and the relation between Thursday drinking and Friday classes overall and for specific vulnerable groups. Methods: A sample of 3,341 volunteer participants was drawn from 3,713 eligible first‐time undergraduates (56% female, 90% non‐Hispanic white). Eligible participation rates ranged from 66.5 to 74.0% across follow‐ups; 90% contributed data at for least one follow‐up. Precollege survey and web‐based surveys administered in the fall and spring semesters across 4 years of college were merged with student academic transcripts and university academic schedules at a large Midwestern public university. The main outcome measures included past 7‐day self‐reports of drinking behavior for each of 8 semesters. Results: Excessive drinking on Thursday, relative to other weekdays, was found and was moderated by Friday class schedule: hierarchical linear models indicated that students with no Friday classes drank approximately twice as much on Thursdays as students with early Friday classes (i.e., mean drinks=1.24 for students with early Friday class vs 2.41 for students with no Friday class). Students who had classes beginning at 12 pm. or later consumed similar amounts as those with no Friday classes (M=2.52). The magnitude of the Friday class effect was comparatively larger among males and among those who were members of the Greek system or participated in Greek activities. Ancillary analyses based on the subset of students who showed within‐subject variability in Friday classes across semesters (i.e., had both early and late or no Friday classes) produced findings similar to those based on the entire sample. Little evidence was found for compensatory drinking on Friday and Saturday among those with early Friday classes. Conclusions: Rates and amounts of alcohol consumption on Thursday are high, although they appear to be influenced by the presence and timing of Friday classes. Friday classes, especially those before 10 am, may reduce excessive drinking. Controlled institutional interventions are suggested to provide definitive research on the causal status of these ostensibly strong effects. This research provides a strong rationale for conducting such research.